CONSTRUCTION OF A GENERALIZED CONTINUOUS MODEL OF A FLYBACK CONVERTER - Yakimenko , I; Karshiboev , Sh (Uzbekistan Open Conference, 2025)
The article presents a methodology for synthesizing a generalized continuous model of a flyback converter for continuous and discontinuous conduction modes of an inductive storage device. The presented results can be used for the synthesis of control systems for flyback, inverting, and buck-boost converters. The methodology proposed in the article can be used for constructing continuous models and designing control systems for buck and boost topologies.
Keywords: generalized continuous model; state-space averaging method; flyback converter; control system synthesis